Fourier transform infrared spectroscopy detects distinct TAR DNA-binding protein 43 signatures in frontotemporal lobar degeneration - Gatto, Rodolfo G.; Gakh, Oleksandr; Wilkins, Jordan M.; Carlos, Arenn F.; Youssef, Hossam; Guo, Yong; Whitwell, Jennifer L.; Josephs, Keith A.; Lucchinetti, Claudia F. (Frontiers in Neuroscience, 2025)
BackgroundFrontotemporal lobar degeneration (FTLD) is a leading cause of cognitive impairment in young adults. A major pathological subtype of FTLD is characterized by positive expression of TAR DNA Binding Protein 43 (TDP-43), referred to as FTLD[TDP]. However, techniques that can be utilized to interrogate and distinguish between various subtypes of FTLD are limited. Herein, we evaluated the potential of Fourier transform infrared (FTIR) spectroscopy to inform on the biomolecular changes in FTLD and to discriminate this disease from other non-FTLD cases.MethodsHistopathologically confirmed cases from FTLD[TDP] and Alzheimer’s disease (AD) autopsy cases were evaluated using FTIR spectroscopy. Formalin-fixed paraffin-embedded (FFPE) brain tissue sections from the superior and medial temporal lobes were obtained from a single control case, an AD case, an FTLD[TDP] case, and a comorbid FTLD[TDP] case that presented with AD pathology (tau and β-amyloid; FTLD[TDP] + AD). All samples were immunostained for pathological forms of tau, β-amyloid, and TDP-43. Myelin was assessed by proteolipid protein staining. Consecutive tissue sections were scanned by FTIR spectroscopy. Spectral maps were manually segmented, matching ten grey matter (GM) and ten white matter (WM) subregions per case for analysis. Peak-area ratios from lipid and amide functional groups as detected by FTIR spectroscopy were quantified and compared.ResultsRelative to the control tissue, both FTLD cases and AD showed increased ratios of amide I/II, α-helix/unordered proteins, α-helix/phosphorylated proteins, and olefinic/lipid content in GM and WM. The α-helix/unordered ratio was significantly different between FTLD cases and AD, while α-helix/unordered and α-helix/phosphorylated ratios differed significantly between FTLD[TDP] and FTLD[TDP] + AD. Across all cases and brain subregions, FTIR spectroscopy-derived amide I/II, olefinic/lipid, and carboxyl/lipid ratios significantly correlated positively with TDP-43 and tau immunoreactivity (p-value < 0.05).ConclusionFourier transform infrared spectroscopy of FFPE brain tissue sections from FTLD[TDP] and AD captures disease-specific changes in the composition of proteins, lipids, and secondary structures. These findings suggest that FTIR spectroscopy can serve as a rapid and cost-effective tool for mapping and quantitating biomolecular alterations in FTLD.